The diffusion of Material Flow Cost Accounting (MFCA) in a small and medium-sized enterprise (SME) automotive vendor in Malaysia - Farizah binti Sulong (Kuliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Material Flow Cost Accounting (MFCA) has attracted growing interest particularly after its ISO 14051 issuance in September 2011. Its evident simultaneous achievement of environmental and economic goals had also appealed to Malaysia through a pilot project with five model SMEs, coordinated by Malaysia Productivity Corporation (MPC). The significant presence of SMEs in Malaysia of 97%, their commonly-held traditionalist views, and their potential to adversely affect the natural environment has stimulated a need to obtain deeper understanding of the MFCA case. Employing a qualitative inquiry, this explanatory case study sought to explain the drivers and innovation-diffusion process of MFCA within the context of one of the model companies, Alpha, an SME automotive vendor. Principally framed by the diffusion of innovation (DOI) theory and supplemented by new institutional sociology (NIS), the study covered periods both during and after the project, and found that Alpha continued its MFCA activities, extending it to several other areas. MFCA in Alpha went through a pseudo-reinvention and was eventually routinised as part of Alpha's continuous improvement activities. Primarily driven towards MFCA by competitive isomorphism to meet cost reduction and competitive pricing criteria, an environment-driven criterion was only secondary for Alpha. Furthermore, institutional pressures were also found in terms of indirect coercive and normative isomorphism from MPC. Various enablers and barriers also contributed to the routinisation of MFCA in Alpha. These include innovation attributes of MFCA, data availability and unavailability, communication via change agencies and champions, team composition, ineffective performance measurement system (PMS) and inadequate human resource training. The study largely contributes to addressing environmental issues by providing insights to potential adopters among SMEs which are in similar contexts to Alpha, and insights to potential change agencies of MFCA. In particular, it provides further evidence to support the revisionist view that performing environmental initiatives can improve economic performance. The study also enriches the literature on MFCA and sustainability management in SMEs with its theoretically-informed empirical research covering both pre- and post-intervention periods. Finally, it also adds value to diffusion research by combining both DOI and NIS of explanations on innovation motivation. The theoretical underpinning was able to explain the pseudo-reinvention and routinisation of MFCA in Alpha. This routinisation also provided insights related to design issues for future research and future MFCA communication programmes.